The Structure of the Decoration in Scenes Executed on Andalusia Islamic Ceramics - Jinan Ali Mohammad Al-Humairi (Zanco Journal of Human Sciences, 2025)
The research dealt with (The structure of the decoration in scenes executed on Andalusia Islamic ceramics), which is divided into four chapters. The first chapter included the research problem that was summarized in the possibility of answering the following question: (Is there a structure of decoration in the Andalusia Islamic ceramic form and what are the mechanisms of its operating in the Islamic ceramic work? while the importance of the research and the need for it (came because this study benefits those with artistic and aesthetic interests, researchers and art connoisseurs in the fields of Islamic ceramic art, also this research provides the opportunity for students and connoisseurs of Islamic art and those interested in its experiences to view the products of Islamic art. The research is characterized by diversity and richness in the formal structure through Shedding light on the products of Islamic art). The aim of the study is to (Identifying the structure of decoration in the scenes executed on Andalusia Islamic ceramics). The researcher identifies the ceramic works executed in Andalusia and includes the specific time period of the century (15-16 AD). As for the second chapter, it was represented by the theoretical framework, including two sections on the first section: (The structure of decoration, a conceptual approach) while the second section was concerned with studying Islamic Andalusian ceramics (its historical references), and the theoretical framework concluded with a set of indicators. The third chapter dealt with the research procedures, which included the research population, selecting the research sample, and analyzing the sample. While the fourth chapter included the research results and conclusions, as well as recommendations and proposals, some of the results reached by the researchers are :- 1- The formal structures appeared in Andalusia Islamic ceramics, whether geometric, plant or animal, as distinctive decorations on ceramic vessels. 2- Rhythm, repetition and symmetry played a prominent role in demonstrating the concept of decoration on all surfaces of Andalusia Islamic ceramics. 3- Shapes, lines and colors intertwined to show the (Ceramic decoration) in superior appearance, especially on the surfaces of Islamic Andalusia ceramic jugs. The most important conclusions reached by the researcher: 1-The Andalusia Islamic potter succeeded in successfully employing the elements of ceramic construction within an environment geographically different from the other Islamic environments. 2- Andalusia Islamic ceramics and the metallic luster were influenced by pictorial scenes from reality that were executed in a very precise, aesthetic and symbolic way, especially when decoration was used to achieve them.